Methicillin-resistant Staphylococcus aureus (MRSA) sepsis complicated by warm autoimmune haemolytic anaemia secondary to antimicrobial therapy - Verdecia, Jorge (BMJ Case Rep, 2019)
A 61-year-old Caucasian woman presented to the emergency room complaining of left-sided chest pain and altered mentation for 3 days. Her medical history included liver cirrhosis and coronary artery disease. On admission, she was found to have methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia. Due to a decline in mental status, a lumbar puncture was performed and cerebrospinal fluid cultures grew MRSA. She was treated initially with vancomycin. Ceftaroline was later added, due to the high burden of disease and difficulty in clearing her infection. After initiation of ceftaroline, bacteraemia cleared and mental status improved, however, she developed haemolytic anaemia. Ceftaroline was stopped and vancomycin continued. Staphylococcal meningitis is a rare occurrence, estimated at a rate of only 1%–10% of all bacterial meningitis cases. Ceftaroline seems to be a suitable option for disseminated MRSA infection, including MRSA meningitis, when the clinical response to vancomycin is inadequate. Further studies are warranted in order to establish adequate dosing while avoiding adverse effects.